(untitled) (Research, Society and Development, 2022)
Breast milk is a very important food that brings numerous benefits to the health and development of the baby, and its exclusivity in the first six months of the individual’s life is recommended. In this context, there is a concern about early weaning, since it can lead to an increase in childhood morbidity and mortality rates, causing a serious public health problem. In view of this, this work aims to highlight the importance of breastfeeding as well as its impacts on the health of the mother and baby. This is a literature review, with a qualitative approach, carried out in the online databases Scientific Electronic Library Online (SciELO), Virtual Health Library (BVS) and National Library of Medicine (PubMED). Based on the scientific evidence investigated, it was found that breastfeeding, in addition to nourishing, acts on the child’s immune system, promotes physical, mental and psychological health for the child and the mother, through the interaction and bond established during breastfeeding. In this way, the importance of raising awareness among mothers through the guidance of health professionals on the subject was observed, so that this assistance occurs from prenatal to postpartum.